Living Reviews in Solar Physics - Solanki, S.K
Living Reviews in Solar Physics is a peer-reviewed, platinum open-access journal, publishing reviews of research in all areas of solar and heliospheric physics. Articles are solicited from leading authorities and are directed towards the scientific community at or above the graduate-student level. The articles in Living Reviews provide critical reviews of the current state of research in the fields they cover. They evaluate existing work, place it in a meaningful context, and suggest areas where more work and new results are needed. Articles also offer annotated insights into the key literature and describe other available resources. Living Reviews is unique in maintaining a suite of high-quality reviews, which are kept up-to-date by the authors. This is the meaning of the word "living" in the journal's title. Living Reviews in Solar Physics attracts readers from the entire solar and heliospheric physics community. Graduate students can use the journal to start their initial literature surveys or to learn about fields peripheral to their own; researchers can use it to quickly find out about the most up-to-date results in fields in which they are not current, to track down bibliographic references that they have not recorded, or even to find areas in which their own skills can be applied in a new field; and lecturers can use it to find information and visual materials that can be used in presentations at all levels.